Pre-Operative Evaluation of Risk Factors for Difficult Laparoscopic Cholecystectomy - Sah, Chandrika; Pokharel, Nabin; Paudel, Prakash; Shrestha, Sunil; Alam, Shahid; Yadav, Aditya Prakash; Singh, Rahul (Nepal Medical College Journal, 2024)
Cholelithiasis or the gallstone disease is the most common biliary pathology. 10-15% population of western world is estimated to be affected by gallstone disease, of which majority remains asymptomatic (>80%) and 1-2 % of these asymptomatic patients will develop symptoms needing surgery per year. In this prospective study, 77 patients years undergoing elective Laparoscopic Cholecystectomy (LC) and meeting all inclusion criteria in Department of General Surgery, Nepal Medical College and Teaching Hospital over period of 1 year. History, detailed clinical examination and laboratory investigations were performed as per the working proforma. Operative time and conversion to open cholecystectomy were recorded. The association between clinical, laboratory and sonographic factors with difficult laparoscopy were obtained. Data analysis was done using SPSS-17 version. Out of 77 patients, 63 were females. Body mass index (BMI) above 30 representing obese population were 33.2% with p value 0.0004. Also, 41.5% patients had history of acute cholecystitis while 12.9% patients had previous history of abdominal surgery and 70.1% patients had history of recurrent abdominal pain. Total of 19.4% patients had increased leucocyte count. On ultrasonography thickened GB wall of >3 mm was seen in 42.8%, distended GB was seen in 41.5%, stone size of >1 cm was seen in 70.1% patients and multiple stones were seen in 84.4%. Similarly, duration of surgery was >90 mins in 31.1% and 7.04% patients underwent conversion to open cholecystectomy both of which were considered difficult laparoscopy. Our study reveled that clinical factors like age, BMI, history of acute cholecystitis, previous history of recurrent abdominal pain and past history of abdominal surgery had significant association in prediction of difficult LC.